2017
DOI: 10.1038/s41598-017-01056-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of late sodium current suppresses calcium-related ventricular arrhythmias by reducing the phosphorylation of CaMK-II and sodium channel expressions

Abstract: Cardiac arrhythmias associated with intracellular calcium inhomeostasis are refractory to antiarrhythmic therapy. We hypothesized that late sodium current (I Na) contributed to the calcium-related arrhythmias. Monophasic action potential duration at 90% completion of repolarization (MAPD90) was significantly increased and ventricular arrhythmias were observed in hearts with increased intracellular calcium concentration ([Ca2+]i) by using Bay K 8644, and the increase became greater in hearts treated with a comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…While discussing CaMKII, it is also important to discuss the late Na + current. Recent work has shown that inhibition of this current is able to suppress Ca 2+ related arrhythmias by reducing CaMKII phosphorylation ( Wei et al, 2017 ). Furthermore, ranolazine, an agent that inhibits both late Na + and K + channels has been shown to have antiarrhythmic effects in the intact heart in CHF and, interestingly, was not associated with drug-induced proarrhythmia ( Frommeyer et al, 2012 ).…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…While discussing CaMKII, it is also important to discuss the late Na + current. Recent work has shown that inhibition of this current is able to suppress Ca 2+ related arrhythmias by reducing CaMKII phosphorylation ( Wei et al, 2017 ). Furthermore, ranolazine, an agent that inhibits both late Na + and K + channels has been shown to have antiarrhythmic effects in the intact heart in CHF and, interestingly, was not associated with drug-induced proarrhythmia ( Frommeyer et al, 2012 ).…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…Though less common, some drugs prolong the QT C interval by increasing I NaL [7,8]. Basic science studies also show that delayed repolarization and ventricular arrhythmias can occur by pharmacologically enhancing I CaL [9]. Knowledge of drug effects on inward and outward ventricular ionic currents is thus important for proarrhythmia risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…found that PLC activity can increase Ca 2+ , thereby activating the apoptotic signal pathway 20 . Furthermore, severe increases in cytosolic Ca 2+ concentration could stimulate Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) 21 . CaMKII, an important member of the calcium/calmodulin-activated protein kinase family, plays a vital role in the regulation of both neuronal death and neuronal survival 22 .…”
Section: Introductionmentioning
confidence: 99%